Profil Penggunaan Obat dalam Penatalaksanaan Hipertensi: Bukti dari Puskesmas Selajambe Tahun 2025 - Rahmat Ripaldi; Yanti Cahyanti; Imat Rochimat; Rani Rubiyanti (STIKes Persada Husada Indonesia, 2026)
Background: Hypertension is a non-communicable disease with a high prevalence in Indonesia and remains a major risk factor for cardiovascular diseases. The increasing number of hypertension cases at Selajambe Public Health Center highlights the importance of evaluating antihypertensive drug utilization to ensure rational and appropriate pharmacotherapy. Objectives: This study aimed to describe the utilization of antihypertensive drugs by patient characteristics, drug classes, drug types, active ingredients, dosages, dosage frequency, and treatment patterns at Selajambe Public Health Center, Kuningan Regency, in 2025. Methods: This descriptive observational study employed a quantitative approach using retrospective data obtained from medical records. A total of 146 hypertensive patients were selected from a population of 230 patients using purposive sampling. Data were analyzed descriptively and presented as frequency distributions and percentages. Results: Most patients were aged over 60 years (56.16%) and female (72%). Monotherapy was the predominant treatment pattern (75%). Calcium Channel Blockers (CCBs), particularly amlodipine, were the most frequently prescribed antihypertensive drugs (75%), followed by Angiotensin-Converting Enzyme Inhibitors (ACEIs), namely captopril (20%), while combination therapy accounted for 5% of prescriptions. Amlodipine was predominantly prescribed at doses of 5 mg (45%) and 10 mg (29%), whereas captopril, an Angiotensin-Converting Enzyme Inhibitor (ACEI), was prescribed at 12.5 mg (26%). Most antihypertensive medications were administered once daily. Conclusion: Antihypertensive drug utilization at Selajambe Public Health Center was predominantly based on CCB monotherapy with amlodipine, which is consistent with current hypertension treatment recommendations, particularly for elderly patients, indicating that single-drug therapy remains the primary treatment approach